Squamous Cell Carcinoma on Marginal Palmar Keratoderma - Freitas de Oliveira Góes, Heliana; Almeida Issa, Maria Claudia; Barbosa Luz, Flávio; dos Santos Lima, Caren; Kalil Aidé, Márcia; Corrijo Rochael, Mayra; Duarte Bezerra Pinto, Roberta (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Marginal palmar keratoderma is characterized by palmar keratoderma affecting the limits of the dorsal and palmar regions of ulnar and radial edges in patients with intense sun exposure. According to the literature it is not considered a pre-malignant lesion. Nevertheless, we report the first case of squamous cell carcinoma on marginal palmar keratoderma in a 57 year-old woman.